2022
DOI: 10.9734/ijpss/2022/v34i1731042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morphological Variation, Grouping and Path Coefficient Studies in a Set of Maize Inbred Lines Local to North East Hill Region of India

Abstract: In the current study a total of 191 maize inbred lines were set up in an augmented randomized complete block design to study the genetic variation and interrelationship of different yield contributing parameters. Observations were recorded on a total of nine phenological and ear / kernel related traits. Significant results for ANOVA indicated presence of substantial variation while the first three axes of PCA could explain 75.54% of the variation present. Ear and flowering traits were orthogonal to each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Path coefficient analysis revealed that days to tasseling (0.0108), ear diameter (0.0057), number of kernels per row (0.0058), 100-seed weight (0.0122), shelling percentage (0.1439), cob yield per plant (1.0014), germination 1 st count (0.0094), seed vigour index-1 (0.0131), seed vigour index-2 (0.0125) and speed of germination (0.0060), had a positive direct effect on grain yield per plant, implying that selecting for these characteristics would likely to result in an overall improvement in grain yield per plant. Similar findings were reported by [4], [12], [14] and [19] for days to 50% tasseling, ear diameter, number of kernels per row, cob yield per plant, [20] for 100 seed weight, [15] for Shelling percentage, [18] for seed vigour traits in soyabean. As a result, it is advised that these characteristics should be prioritized in the yield improvement programme.…”
Section: Resultssupporting
confidence: 86%
“…Path coefficient analysis revealed that days to tasseling (0.0108), ear diameter (0.0057), number of kernels per row (0.0058), 100-seed weight (0.0122), shelling percentage (0.1439), cob yield per plant (1.0014), germination 1 st count (0.0094), seed vigour index-1 (0.0131), seed vigour index-2 (0.0125) and speed of germination (0.0060), had a positive direct effect on grain yield per plant, implying that selecting for these characteristics would likely to result in an overall improvement in grain yield per plant. Similar findings were reported by [4], [12], [14] and [19] for days to 50% tasseling, ear diameter, number of kernels per row, cob yield per plant, [20] for 100 seed weight, [15] for Shelling percentage, [18] for seed vigour traits in soyabean. As a result, it is advised that these characteristics should be prioritized in the yield improvement programme.…”
Section: Resultssupporting
confidence: 86%
“…High significant positive correlation with yield per plant was recorded by number of cobs per plant followed by ear length, number of grains per row, 100 grain weight, harvest index, biological yield, suggesting that indirect selection for high yield through direct selection for these characters will be highly effective (Table 3). Similar type of results for number of grains per row [18][19][20], number of cobs per plant [21], ear length [22,23], 100 grain weight [24,25], harvest index [26]. Flowering traits like days to 50% tasseling and days to 50% silking showed significant negative correlation with grain yield.…”
Section: Resultsmentioning
confidence: 57%
“…In view of the general combining ability results different parental lines under HS condition, no parental line showed great combiners for every one of the characteristics thus, parental line P 7 showed great general combining ability for each and every characters with the exception of seed index and starch content [23][24][25][26][27].…”
Section: General Combining Ability Analysismentioning
confidence: 99%